2012
DOI: 10.2479/swex.15.1
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intensity and determinants in basic aquabics movements

Abstract: 〔abstract〕The aims of this study were to determine the exercise intensity of basic aquabics exercises and to examine the determinants of exercise intensity from physical characteristics such as body size and physical fitness. Thirty-eight young men (11 sedentary, 15 endurance-trained, and 12 resistance-trained men) were participated in the study. They performed 4 basic aquabics exercises in a swimming pool, which the water depth was at the level of xiphoid process, for 5 minutes each and oxygen uptake were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…During water exercise, it could be established that the heart rate, oxygen uptake and body temperature respond to the influence of the physical characteristics of water (water pressure, temperature, buoyancy, viscosity, etc) . Previous studies demonstrated physiological responses to changes in the physical characteristics of water, and that such responses differed from those coming from landbased exercise [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] . We introduce the theory that physiological response benefits from water exercise, and explain its practical use for health promotion.…”
Section: Introductionmentioning
confidence: 99%
“…During water exercise, it could be established that the heart rate, oxygen uptake and body temperature respond to the influence of the physical characteristics of water (water pressure, temperature, buoyancy, viscosity, etc) . Previous studies demonstrated physiological responses to changes in the physical characteristics of water, and that such responses differed from those coming from landbased exercise [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] . We introduce the theory that physiological response benefits from water exercise, and explain its practical use for health promotion.…”
Section: Introductionmentioning
confidence: 99%